Coupling Inner and Outer Body for Self-Consciousness. Issue 5 (May 2019) - Park, Hyeong-Dong; Blanke, Olaf
Abstract : Although recent studies on self-consciousness emphasized the importance of bodily processing and multisensory integration, such research has focused solely on bodily signals originating from the outside of the body (i.e., exteroceptive bodily signals) or internal bodily signals from visceral organs (i.e., interoceptive bodily signals) and how each system contributes to self-consciousness, without much interaction between the two approaches. Reviewing the latest evidence on interoceptive bodily processing and the combination of exteroceptive and interoceptive bodily signals for self-consciousness, we propose an integrated neural system reconciling these two largely separated views and delineate how it accounts for fundamental aspects of self-consciousness such as self-identification and self-location, as well as its experienced global unity and temporal continuity. Highlights: We review behavioral, neuroimaging, neurological, and electrophysiological evidence suggesting that interoceptive bodily signals and their neural processes are of fundamental importance for bodily self-consciousness (BSC). Superseding previous proposals on separate neural systems for BSC based on either exteroceptive (e-BSC system) or interoceptive (i-BSC system) signals, the reviewed data further show that the classical nodes of both the e-BSC system and the i-BSC system are commonly involved in experimentally and neurologically altered states of BSC. We propose a torso-centered BSC system – based on integrated exteroceptive and interoceptive bodily signals from the trunk – and delineate how it accounts for fundamental aspects of self-consciousness such as self-identification and self-location, as well as its experienced global unity and temporal continuity.